Causal associations between gut microbiota and Cholestatic liver diseases: a Mendelian randomization study - Yang, Jiaqi; Ma, Gang; Wang, Kemei; Yang, Hui; Jiang, Shuangshuang; Fan, Qingling; Zhou, Xinmin; Guo, Guanya; Han, Ying (Frontiers in Medicine, 2024)
The etiological factors of Cholestatic Liver Diseases especially primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC) are not fully illustrated. It has been reported in previous observational studies that gut microbiota are associated with cholestatic liver diseases.However, there is uncertainty regarding the causality of this association. By using Mendelian 2 randomization, this study aimed to examine the causal impact of gut microbiota on cholestatic liver diseases.Methods: From large-scale genome-wide association studies, genetic instruments for each gut microbiota taxa as well as primary biliary cholangitis and primary sclerosing cholangitis were developed. Subsequently, we conducted a two-sample Mendelian randomization analysis, supplemented by multiple post hoc sensitivity analyses. Additionally, we performed reverse MR analyses to investigate the possibility of the reverse causal association.Result: This two-sample MR study indicated that the order Bacillales, family Peptostreptococcaceae, family Ruminococcaceae, genus Anaerotruncu was associated with a decreased risk of developing PBC, and that order Selenomonadales, family Bifidobacteriaceae may be factors that increase the risk of PBC. On the other hand, we also identified order Selenomonadales, family Rhodospirillaceae, and genus RuminococcaceaeUCG013 were positively associated with PSC. The order Actinomycetales, family Actinomycetaceae, genus Actinomyces, genus Alloprevotella, genus Barnesiella, and genus Peptococcus were found negative associations with the risk of PSC. The reverse MR analysis demonstrated no statistically significant relationship between PBC, PSC and these specific gut microbial taxa.Our findings offered novel evidence that the abundance of particular bacteria contributes to the risk of PBC and PSC, which may contribute to more effective approaches to PBC and PSC therapy and prevention.